2014
DOI: 10.1123/ijatt.2013-0096
|View full text |Cite
|
Sign up to set email alerts
|

Physician Satisfaction With Residency-Trained Athletic Trainers as Physician Extenders

Abstract: Athl etic trainers (ATs) have historically functioned in a physician extender role when managing the health of competitive athletes in high school, collegiate, and professional settings. A high level of expertise in the prevention and management of musculoskeletal disorders among physically active individuals has been recognized by physicians who have chosen to utilize ATs as physician extenders in orthopedic and sports medicine clinical operations. The development of postprofessional residency programs that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Previous studies have found ATs functioning in the physician clinic setting increase clinical efficiency by 15%-30% 1,3-6 (ie, patient volume and revenue generation), improve patient outcomes, 16 and increase physician satisfaction. 2,5,7 A recent article revealed that patients compared ATs with orthopaedic medical residents in both perceived level of musculoskeletal knowledge and patient care. 8 Health care changes placing more emphasis on preventive care make the AT an ideal fit for filling the gap reported in primary care access.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found ATs functioning in the physician clinic setting increase clinical efficiency by 15%-30% 1,3-6 (ie, patient volume and revenue generation), improve patient outcomes, 16 and increase physician satisfaction. 2,5,7 A recent article revealed that patients compared ATs with orthopaedic medical residents in both perceived level of musculoskeletal knowledge and patient care. 8 Health care changes placing more emphasis on preventive care make the AT an ideal fit for filling the gap reported in primary care access.…”
Section: Discussionmentioning
confidence: 99%
“…Athletic trainers in the physician practice setting have gained significant recognition and popularity in the health care community in recent years. [1][2][3][4][5][6][7][8] The development of postprofessional programs that provide advanced experience and education in the physician practice model has given ATs the opportunity to learn how to function effectively and efficiently in this setting. The Commission on Accreditation of Athletic Training Education (CAATE) has developed standards 9 that guide the didactic and clinical experiences for postprofessional residency (PPR) programs within a clinical area of focus.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The development of postprofessional athletic training residencies (PP-ATRs) has given athletic trainers the opportunity to advance their skills. The goal of the athletic training residency is to provide advanced preparation of athletic training practitioners through a planned program of clinical and didactic education in specialized content areas using an evidence-based approach to enhance the quality of patient care, optimize patient outcomes, and improve patients' health-related quality of life.…”
Section: Self-funding a Postprofessional Athletic Training Residencymentioning
confidence: 99%
“…1,3,[9][10][11][12][13][14] The use of athletic trainers in the orthopaedic clinic setting has grown exponentially over the last decade. [1][2][3][9][10][11][12][13][14][15][16] Educational programming offered in PP-ATR build upon the athletic trainers' foundational knowledge in CE, preparing them be effective clinicians when entering the workforce.…”
Section: Athletic Training Residenciesmentioning
confidence: 99%
“…5 ATs not only increased throughput, but also improved patient satisfaction; increases in their self-reported health levels as well as improved quality of life for physicians were noted. 6,7 ATs may be contributing to improved productivity because athletic training skill sets are well-aligned with the needs of the patients seen in ambulatory care settings. For example, patients seen in orthopedic practices may require care for a musculoskeletal condition, which is one of the domains of education for ATs.…”
Section: Introductionmentioning
confidence: 99%